Strategi Digital Marketing Melalui Marketplace Pada UMKM CV. Rapoviaka Simple - Rini Yuliana; Maskuri Sutomo ; Ira Nuriasanti ; Wiri Wirastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the current era, digital marketing has become one of the marketing strategies used by business people today, digital marketing has become a solution for business people to expand their business environment, both micro and macro business people. The aim of this research was to determine and analyze digital marketing strategies in marketplaces (Shopee and Tokopedia) to market products and identify existing strengths, weaknesses, opportunities and threats using SWOT analysis. The method used in this research is qualitative. Simple Rapoviaka has just created a marketing strategy through the Shopee marketplace and Tokopedia to increase its market share, implementing digital marketing carried out by CV. Rapoviaka simple aims to increase sales. This is because consumers are wider, closer, and check the quality and reputation of products, using online transactions. This could be an example for other MSMEs, where CV. Rapoviaka Simple itself is still distributing its products to its marketing partners, namely Palu souvenir shops offline and now they are selling